Patterns of extreme temperature-related catastrophic events in Europe including the Russian Federation: a cross-sectional analysis of the Emergency Events Database - Brennenstuhl, Heiko; Will, Manuel; Ries, Elias; Mechler, Konstantin; Garbade, Sven; Ries, Markus (BMJ open, 2021)
To investigate reported extreme temperature-related catastrophic events and associated mortality on the European continent including the Russian Federation. Cross-sectional respecting Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) criteria.Data source: Emergency Events Database (EM-DAT). Search criteria: location—European continent including Russian Federation, time—years 1988 until 2019 (close of database 12 July 2019), catastrophic events—extreme temperatures. Primary outcome measures Numbers of heat waves, cold waves, severe winter conditions and associated number of deaths, overall, and per country and year, respecting STROBE criteria. The most frequent type of the 243 events recorded in EM-DAT were cold waves (54.7%). However, cold waves and severe winter conditions only accounted for 6460 deaths (4.5%), while heat waves were associated with 137 533 deaths (95.5%). The five most severe heat waves in 2003, 2006, 2010, 2013 and 2015 were associated with a total of 135 089 deaths. The most severe heat waves were geographically distributed over the Russian Federation (2010), as well as France, Italy, Spain and Germany, each in 2003. Although cold waves are more frequently reported in EM-DAT, heat waves are the major cause for temperature-related deaths. In order to better protect the public, it is important to address resiliency and vulnerability of populations at risk and age groups.